Expression of PD-L1 and p-RPS6 in epithelial dysplasia and squamous cell carcinoma of the oral cavity - Hanroongsri, Jaruwat; Amornphimoltham, Panomwat; Younis, Rania H.; Chaisuparat, Risa (Frontiers in Oral Health, 2024)
Oral squamous cell carcinoma (OSCC) is often preceded by oral epithelial dysplasia (OED).The role of ribosomal protein S6 (RPS6) and programmed cell death ligand-1 (PD-L1) in the progression of OED to OSCC remains unclear. This study aimed to investigate the expression of phosphorylated RPS6 (p-RPS6) and PD-L1 in OSCC and OED and to examine its relationship with clinicopathological features. Fifty-two OSCC and 48 OED cases were recruited for immunohistochemical analysis of p-RPS6 and PD-L1 expression. The expression of markers was correlated with clinicopathological features of OSCC and OED.We found p-RPS6 expression in all cases of OSCC and OED, whereas PD-L1 was expressed in 42/48 (87% ) OED and in 28/52 (53% ) OSCC. The patients with mild OED presented higher expression level of PD-L1 and p-RPS6 significantly, when compared to moderatedifferentiated OSCC patients (P<0.05). Moreover, we found a significant positive correlation between PD-L1 and p-RPS6 expression in OED and OSCC patients (p<0.01).The PD-L1 expression was significantly related to more than 2 cm tumor size in OSCC patients (p=0.007). Our findings suggest the upregulation of PD-L1 may be related with activation of the mTOR pathway in the early events of tumor progression and the pathogenesis of OSCC.